Green mobility 4.0:- Where are we heading? - Motowidlak, Urszula (W poszukiwaniu zielonego ładu, 2022)
The aim of the chapter is to indicate the technological, organizational and social solutions that have a high potential in shaping the model of “green” mobility 4.0 in the Smart ecosystem. Selected factors shaping the development of the new mobility ecosystem were analyzed. The results of the studies carried out indicate that innovations and business models in mobility systems are undergoing fundamental changes thanks to the new generation of consumers who expect value co-creation.